2017
DOI: 10.1105/tpc.17.00020
|View full text |Cite
|
Sign up to set email alerts
|

Intron DNA Sequences Can Be More Important Than the Proximal Promoter in Determining the Site of Transcript Initiation

Abstract: To more precisely define the positions from which certain intronic regulatory sequences increase mRNA accumulation, the effect of a intron on gene expression was tested from six different positions surrounding the transcription start site (TSS) of a reporter gene fusion in The intron increased expression from all transcribed positions but had no effect when upstream of the 5'-most TSS. While this implies that the intron must be transcribed to increase expression, the TSS changed when the intron was located in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 51 publications
(88 reference statements)
6
61
0
2
Order By: Relevance
“…Effects on antisense transcription in these mutant cell lines mirrored those observed for sense transcription ( Figure 3C), suggesting that inclusion of the new exon enhances transcription from the upstream promoter in both directions. This pattern is distinct from some observations of intron-mediated enhancement in which sense-oriented introns specifically inhibited antisense transcription (Agarwal and Ansari, 2016), but is consistent with reported impacts on transcription initiation resulting from changes in the position of an intron in a reporter gene (Gallegos and Rose, 2017).…”
Section: Manipulation Of Exon Splicing Impacts Upstream Transcriptionsupporting
confidence: 77%
“…Effects on antisense transcription in these mutant cell lines mirrored those observed for sense transcription ( Figure 3C), suggesting that inclusion of the new exon enhances transcription from the upstream promoter in both directions. This pattern is distinct from some observations of intron-mediated enhancement in which sense-oriented introns specifically inhibited antisense transcription (Agarwal and Ansari, 2016), but is consistent with reported impacts on transcription initiation resulting from changes in the position of an intron in a reporter gene (Gallegos and Rose, 2017).…”
Section: Manipulation Of Exon Splicing Impacts Upstream Transcriptionsupporting
confidence: 77%
“…In genomes of animals, plants, fungi, and protists, intron positions could be conserved throughout prolonged evolutionary times, suggesting their involvement in gene expression and regulation, including mRNA processing (46)(47)(48). Numerous studies in animals and plants have emphasized that introns may carry functional cis-acting elements affecting gene expression even in the absence of promoter sequences (49)(50)(51)(52)(53). Recently, it was shown that nucleosomes preferentially occupy exons rather than introns, and this phenomenon seems to be interconnected with specific histone modifications favoring gene expression (54-56).…”
Section: Discussionmentioning
confidence: 99%
“…The most thoroughly analyzed IME intron is the first intron from the Arabidopsis UBQ10 gene. This intron increases mRNA accumulation only when located downstream of the TSS, and can stimulate expression from at least 550 nt from the TSS but not 1,100 nt or more[20,21]. Remarkably, deleting a 300 nt region of the proximal promoter that contains all known TSSs does not diminish the expression of constructs containing this intron [21].…”
Section: Introductionmentioning
confidence: 99%
“…This intron increases mRNA accumulation only when located downstream of the TSS, and can stimulate expression from at least 550 nt from the TSS but not 1,100 nt or more[20,21]. Remarkably, deleting a 300 nt region of the proximal promoter that contains all known TSSs does not diminish the expression of constructs containing this intron [21]. Transcription in these promoter-deleted constructs initiates in normally untranscribed sequences the same distance upstream of the intron as when the promoter is intact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation